New think - "De Bono,Edward" (New York, 1968)
New think is a way of breaking out of these old, self-perpetuating patterns Edward Debono's remarkable method of thinking opens the mind to creative, uninhibited thought by allowing logic to serve your mind, not control it.
Keywords: Psychology